Использование инновационных технологий в учебном процессе в педвузе - Демиденко, Р. Н. (My University, 2016)
In this article, the author examines the current problem the use of innovative technologies in the process of preparing future teachers, paying particular attention to the application of technology student- centered learning and simulation training situations. The author emphasizes that learning situations can be an effective tool in teaching students at all levels
Keywords: educational technology; educational technology; innovative technology; innovation; personality-oriented learning; the educational situation